Change in Physical and Chemical Properties of Soil in Irrigated Eucalyptus Plantation in Gujarat State - Srivastav, A. K. (Indian Forester, 1993)
A study undertaken to find out the effect of Eucalyptus plantation on the soil moisture content, maximum water holding capacity, pH, electrical conductivity, organic carbon, available Phosphorous, available Potash etc. of soil revealed a slight variation in the moisture content and maximum water holding capacity of the soil in planted area. The pH of planted area shifted slightly towards acidic side but the change was not substantial and the soil remained well within the normal limits. Marginal change in the conductivity indicates that Eucalyptus plantation hardly affects the soluble salt content. Any change observed may be due to the leaching effect during irrigation. Likewise the values of organic carbon also remained within similar limits over the different years. There is no appreciable change in the content of available phosphorous. The amount of potash shows fluctuations in different years. A careful examination of the entire data reveals that the changes brought about by Eucalyptus plantation under the local conditions of climate and soil are not damaging to the edaphic condition as apprehanded by many.